PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN, DAN KARAKTERISTIK SITUASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Mahayanti, I Gusti Ayu Komang; Sriathi, Anak Agung Ayu (E-Jurnal Manajemen; Vol 6 No 4 (2017), 2017)
In the era of free competition today many companies are focused on building their employees' job satisfaction, employee satisfaction because they will greatly influence the future development of the company. Low employee satisfaction is one symptom that can cause deterioration in a company. The purpose of this study is to analyze and explain the influence of individual characteristics, job characteristics, the characteristics of the employment situation on employee job satisfaction. The population in this study are employees at Bali Agung Oleh-Oleh Khas Bali. The sampling method used is the census, the number of respondents was 48. The multiple linear regression analysis technique is used as an analytical tool. The results showed that individual characteristics and significant positive effect on employee job satisfaction, job characteristics and significant positive effect on employee job satisfaction, work situation characteristics and significant positive effect on employee job satisfaction.
Keywords: individual characteristics, job characteristics, characteristics situation work, job satisfaction